Implementation and Training on the Use of the Integrated Village Data Management Information System in the Indonesia – Timor Leste Border Area - Frengky Tedy; Yulianti Paula Bria; Paskalis Andrianus Nani; Emiliana M. Meolbatak; Yovinia Carmeneja Hoar Siki; Jaime da Costa Lobo Soares; Apolinario Dos Santos (International Journal Of Community Service, 2025)
Villages in the Indonesia–Timor Leste border area continue to operate their administrative tasks manually, relying on ledger books and Microsoft Word and Excel to manage data. However, with the rapid advancement of technology, these practices have led to less effective public services. To address this issue, a community service initiative was undertaken to implement the Integrated Village Data Management Information System in Weoe Village, aiming to streamline and enhance service delivery to the community. The system is web-based, which improves accessibility for both residents and village officials, allowing them to access data from anywhere with an internet connection. The initiative consisted of three main stages: preparation, implementation, and evaluation. The implementation of this system was successfully completed. System development and training on the use of the integrated village data management information system significantly improved participants' understanding, as evidenced by the comparison of pre-test and post-test scores. Participants’ average scores increased by 34.5 points, from 49 in the pre-test to 83.5 in the post-test among five participants. This web-based village data management information system has proven to be an effective solution for enhancing public services, making them more efficient and impactful.